The Effectiveness the Implementation of the Zero-Based Budgeting in the Saudi Governmental Sectors: An Empirical Study - Al Harbi, Maram Ali; Sejini, Talal Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aims to identify the effectiveness of implementing zero-based budgeting in the Saudi Governmental Sector. In order to achieve this aim, a descriptive analytical approach is applied; through preparing a well thought out questionnaire that was circulated amongst the a sample of executives who are responsible for budget preparation in the public organizations taken. The results of the current study supported the effectiveness in implementing zero-based budgeting in public organizations in the Saudi Governmental Sector. The results of the study specified that the most important advantage of implementing zero-based budgeting is reducing both the wastage of resources and the huge amounts of monetary allocation to public organizations. Yet this was limited by the major need of training human resources to zero-based budgeting. In line with Vision (2030), the researcher recommends further studies of general budgeting methodology to be implemented in the budgeting preparation process of the governmental sector and suggest newer activities and programs in such process. However, the outcome of the research led to more significant recommendations such as firstly, keeping the responsible executives for budgeting up to date on the development and implementation of new concepts in budgeting, secondly, developing a continual professional program for the employees related to budgeting preparation and implementation, and finally, improving continuously the knowledge of new and existing man power concerned with budget and budget preparation in the public organizations.